Non-functioning pituitary macroadenoma following surgery: long-term outcomes and development of an optimal follow-up strategy - Hussein, Ziad; Grieve, Joan; Dorward, Neil; Miszkiel, Katherine; Kosmin, Michael; Fersht, Naomi; Bouloux, Pierre Marc; Jaunmuktane, Zane; Baldeweg, Stephanie E.; Marcus, Hani J. (Frontiers in Surgery, 2023)
Objectives Recurrence and regrowth of non-functioning pituitary macroadenomas (NFPMs) after surgery are common but remain unpredictable. Therefore, the optimal timing and frequency of follow-up imaging remain to be determined. We sought to determine the long-term surgical outcomes of NFPMs following surgery and develop an optimal follow-up strategy. Methods Patients underwent surgery for NFPMs between 1987 and 2018, with a follow-up of 6 months or more, were identified. Demographics, presentation, management, histology, imaging, and surgical outcomes were retrospectively collected. Results In total, 383 patients were included; 256 were men (256/383; 67%) with median follow-up of 8 years. Following primary surgery, 229 patients (229/383; 60%) achieved complete resection. Of those, 28 (28/229; 11%) developed recurrence, including six needed secondary surgery (6/229; 3%). The rate of complete resection improved over time; in the last quartile of cases, 77 achieved complete resection (77/95; 81%). Reoperation-free survival at 5, 10 and 15 years was 99%, 94% and 94%, respectively. NFPMs were incompletely resected in 154 patients (154/383; 40%); of those, 106 (106/154; 69%) had regrowth, and 84 (84/154; 55%) required reoperation. Surgical reintervention-free survival at 5, 10 and 15 years was 74%,49% and 35%, respectively. Young age and cavernous sinus invasion were risk factors for undergoing reoperation (P<0.001 and P<0.0001, respectively) and radiotherapy (P=0.003 and P<0.001, respectively). Patients with residual tumour required reoperation earlier than those underwent complete resection (p=0.02). Radiotherapy to control tumour regrowth was delivered to 65 patients (65/383; 17%) after median time of 1 year following surgery. Radiotherapy was administered more in patients with regrowth of residual disease (61/106; 58%) than those who had NFPMs recurrence (4/28; 14%)(p=<0.001) Following postoperative radiotherapy, one patient (1/65; 2%) had evidence of regrowth, seven (7/65; 11%) had tumour regression on imaging, and no patients underwent further surgery. Conclusions: NFPMs recurrence and regrowth are common, particularly in patients with residual disease post-operatively. We propose a follow-up strategy based on stratifying patients as “low risk" if there is no residual tumour, with increasing scan intervals, or "high risk" if there is a residual tumour, with annual scans for at least five years and extended lifelong surveillance after that.